STRATEGI VISUAL UNTUK UMKM: PELATIHAN FOTOGRAFI PRODUK DAN DESAIN MEDIA SOSIAL BAGI KOMUNITAS IBU RUMAH TANGGA - akkapurlaura, akkapurlaura; Wahyuningrum, R.A Heryani; Armas, Anita; Purnama, Pongky Adhi (Universitas Trisakti, 2025)
This Community Partnership Program (PkM) was initiated in response to the needs of the “Zero Waste and Soap Making” community, consisting of housewives aiming to enhance their digital marketing skills and improve the economic value of their homemade products. Despite actively participating in bazaars around Jakarta and Tangerang, the community lacked the skills to produce attractive product photos and utilize digital visual strategies. This program provided an online training session for 20 participants over two days, covering basic product photography using mobile phones and the use of Canva to design social media content. The training method included lectures, demonstrations, hands-on practice, and feedback on participants’ work. The results showed improved abilities in capturing creative product photos and designing more professional Instagram feeds. This training contributed to the economic empowerment of the community by enhancing the online appeal and marketability of their products.